Nurse 2008. Tense and Aspect in Bantu - Seidel, Frank (AAeO - Afrikanistik-Aegyptologie-Online, 2009)
Derek Nurse 2008. Tense and Aspect in Bantu. Oxford: Oxford University Press. 401 pages, plus two online appendices of all in all 361 pages; 7 maps; 11 tables. € 155,99